Characterization of a de novo SCN8A mutation in a patient with epileptic encephalopathy - de Kovel, Carolien G.F. (Epilepsy Res, 2014)
OBJECTIVE: Recently, de novo SCN8A missense mutations have been identified as a rare dominant cause of epileptic encephalopathies. Functional studies on the first described case demonstrated gain-of-function effects of the mutation. We describe a novel de novo mutation of SCN8A in a patient with epileptic encephalopathy, and functional characterization of the mutant protein. DESIGN: Whole exome sequencing was used to discover the variant. We generated a mutant cDNA, transfected HEK293 cells, and performed Western blotting to assess protein stability. To study channel functional properties, patch-clamp experiments were carried out in transfected neuronal ND7/23 cells. RESULTS: The proband exhibited seizure onset at 6 months of age, diffuse brain atrophy, and more profound developmental impairment than the original case. The mutation p.Arg233Gly in the voltage sensing transmembrane segment D1S4 was present in the proband and absent in both parents. This mutation results in a temperature-sensitive reduction in protein expression as well as reduced sodium current amplitude and density and a relative increased response to a slow ramp stimulus, though this did not result in an absolute increased current at physiological temperatures. CONCLUSION: The new de novo SCN8A mutation is clearly deleterious, resulting in an unstable protein with reduced channel activity. This differs from the gain-of-function attributes of the first SCN8A mutation in epileptic encephalopathy, pointing to heterogeneity of mechanisms. Since Nav1.6 is expressed in both excitatory and inhibitory neurons, a differential effect of a loss-of-function of Nav1.6 Arg223Gly on inhibitory interneurons may underlie the epilepsy phenotype in this patient.